Stroke patients presenting to the emergency department of a tertiary care hospital (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Stroke is one of the most common causes of morbidity and mortality in Nepal. It is the 3rd most common cause of death worldwide. In Nepal Non-communicable diseases in Nepal(NCDs) states that stroke accounts for 42% of all deaths and is estimated to reach about 66.3% of all deaths by 2030.Method: A retrospective cross-sectional study of all stroke patients seen in Patan Hospital Emergency Department for a period of 1 y. Demographic data, presenting complaint, time of onset of symptoms, time presenting to the Emergency, patient’s risk factors for stroke, head CT findings (hemorrhagic or ischemic stroke) were analyzed descriptively. Ethical approval was taken.Result: Total 170 patients (96 males i.e.56.5% and 74 females i.e. 43.5%) were analyzed. 130(76.5%) were ischemic CVA and 40 (23.5%) were hemorrhagic CVA. The most common presenting symptoms was hemiparesis and speech changes.Conclusion: Stroke is a common disease seen in Nepal, with higher percentages of hemorrhagic stroke.